Regulasi Perlindungan Anak di Ruang Digital di Indonesia : Implementasi, Tantangan, dan Peluang Implementasi - Izzatun Khusnaini; Eny Nur Aisyah (Pro Justicia: Jurnal Hukum dan Sosial, 2025)
The development of digital technology has provided both opportunities and risks for children in learning, playing, and socializing in digital spaces. However, children's high exposure to the internet poses potential threats such as data misuse, cyberbullying, online exploitation, and access to age-inappropriate content. In response, the Indonesian government issued Government Regulation No. 17 of 2025 concerning the Governance of Electronic Systems for Child Protection (PP TUNAS) as a legal basis for strengthening child protection in the digital space. This research used a literature review method with a qualitative descriptive approach through a review of regulations, scientific articles, and documents from relevant international institutions. The results show that PP TUNAS provides a clear direction for protection through regulations on age verification, protection of children's personal data, and the application of the principle of safety by design on digital platforms. However, its implementation still faces challenges, particularly related to technological readiness, institutional coordination, and low digital literacy among children and parents. Therefore, the success of the regulation requires strengthening institutional capacity, multi-stakeholder collaboration, and sustainable digital literacy programs that encourage collective awareness in creating a safe digital space that supports children's growth and development.